2019
DOI: 10.1371/journal.pone.0213689
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Brucella field strains isolated from livestock, wildlife populations, and humans in Italy from 2007 to 2015

Abstract: Brucellosis is a major public health problem still prevalent as a neglected endemic zoonosis requiring proactive attention in many communities worldwide. The present study involved analysis of Brucella field strains submitted for typing to the Italian National Reference Laboratory for Brucellosis from 2007 to 2015. Strains were identified at the species and biovar levels by classic and molecular techniques according to the World Organisation for Animal Health Manual. In total, 5,784 strains were typed: 3,089 B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 38 publications
1
58
2
1
Order By: Relevance
“…Movements of infected animals can contaminate feeding and grazing areas and may spread infection to other animals (e.g., cattle, buffalo or camel) [10]. The prevalence of B. melitensis and B. suis in swine may be attributed to the cross-contamination or co-rearing of pigs with other animals [6,15,19,20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Movements of infected animals can contaminate feeding and grazing areas and may spread infection to other animals (e.g., cattle, buffalo or camel) [10]. The prevalence of B. melitensis and B. suis in swine may be attributed to the cross-contamination or co-rearing of pigs with other animals [6,15,19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Human pathogenic biovars (B. suis biovar 1-4) pose a sever hazard to humans [16]. Hence, B. abortus [17,18] and B. melitensis [19,20] were also isolated from pigs when kept together with infected ruminants and camels.…”
Section: Introductionmentioning
confidence: 99%
“…While Bangladesh and Brazil are clearly geographically well separated, it has previously been reported that most of the cattle imported into Brazil are from Europe or India (Minharro et al, 2013). This provides a plausible explanation Brucella from field outbreak and to trace back the source of new strain in a particular geographic area is important to undertake effective control measures against brucellosis (De Massis et al, 2019).…”
Section: Discussionmentioning
confidence: 98%
“…Further analysis with approaches such as whole genome sequencing would help to more categorically establish the relationship of these isolates with the global population. Characterization of the species and biovars of Brucella from field outbreak and to trace back the source of new strain in a particular geographic area is important to undertake effective control measures against brucellosis (De Massis et al, ). The data of species and biovar identification and genetic characterization of Brucella field isolates of the present work may be useful to formulate policy and strategies for the control of bovine brucellosis in Bangladesh.…”
Section: Discussionmentioning
confidence: 99%
“…isolated from wild animals were smooth Brucella spp. [ 6 , 23 , 24 ], the studies on wildlife brucellosis have been limited to some species, specifically in Asian elephants. Consequently, there are less information available for Asian elephant brucellosis.…”
Section: Discussionmentioning
confidence: 99%